2017
DOI: 10.18632/oncotarget.14757
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of canaloplasty versus trabeculectomy in treatment of glaucoma

Abstract: We assess the efficacy and safety of canaloplasty and trabeculectomy for treatment of glaucoma. We searched the China National Knowledge Infrastructure, PubMed, Web of Science, and WanFang databases for potentially eligible studies. Pooled risk ratio (RR) with 95% confidence interval (CI) was calculated using random- or fixed-effect models if appropriate. Eight studies were included for meta-analysis. There was no difference in intraocular pressure at 6 months (WMD = 0.97, 95%CI: -0.48-2.41). Intraocular press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Surgical success after the follow-up period was more than twice as high after trabeculectomy than after modified canaloplasty, independently from how success was defined. Previous studies showed inconsistent findings regarding surgical success: Some studies found similar results to this study with a higher complete success after trabeculectomy [ 12 , 16 , 17 , 18 , 19 ], while in other studies both methods reached comparable results [ 20 , 21 ]. A long-termed follow-up period of up to three years in a mixed cohort was reported by Nassri et al [ 12 ] and there was a similar gap of complete success between canaloplasty and trabeculectomy as in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Surgical success after the follow-up period was more than twice as high after trabeculectomy than after modified canaloplasty, independently from how success was defined. Previous studies showed inconsistent findings regarding surgical success: Some studies found similar results to this study with a higher complete success after trabeculectomy [ 12 , 16 , 17 , 18 , 19 ], while in other studies both methods reached comparable results [ 20 , 21 ]. A long-termed follow-up period of up to three years in a mixed cohort was reported by Nassri et al [ 12 ] and there was a similar gap of complete success between canaloplasty and trabeculectomy as in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…To date, this is the most comprehensive and thorough systematic review and meta-analysis of the comparative e cacy and safety between TE and CP either as standalone or combined with phacoemulsi cation. There are three published systematic reviews and meta-analyses in this regard 11,15,31 . In 2016, Liu et al 15 , analyzed six studies comparing CP to TE, revealing a greater reduction in IOP and a higher complication rate in favor of TE.…”
Section: Discussionmentioning
confidence: 99%
“…There are three published systematic reviews and meta-analyses in this regard 11,15,31 . In 2016, Liu et al 15 , analyzed six studies comparing CP to TE, revealing a greater reduction in IOP and a higher complication rate in favor of TE. Meanwhile, the study of Lin et al 31 , which was published in 2017, yielded con icting results, showing more IOP reduction in the CP group, with no signi cant difference between both groups regarding complete and quali ed success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trabeculectomy is the gold standard of antiglaucoma surgery, but it is associated with a high number of postoperative complications and requires more frequent postoperative intervention. With canaloplasty, the physiological drainage of the aqueous humor through the bead canal is increased by opening or widening of the Schlemm’s canal, without the need to create a functional filtering bleb [ 27 ]. Therefore, the risk of potential pathway for pathogens to enter the eyeball and cause inflammation inside the eyeball is eliminated as well.…”
Section: Discussionmentioning
confidence: 99%